2017
DOI: 10.1016/j.metabol.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Higher free triiodothyronine is associated with non-alcoholic fatty liver disease in euthyroid subjects: the Lifelines Cohort Study

Abstract: Euthyroid subjects with suspected NAFLD are characterized by higher FT3, lower FT4 and higher FT3/FT4 ratio, probably consequent to central obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 50 publications
11
70
1
1
Order By: Relevance
“…3 Two Chinese studies and one Dutch study found a positive association between high-normal FT3 levels and NAFLD, where the latter used the fatty liver index to identify NAFLD. [8][9][10] Our results documented this positive association in euthyroid women but not in euthyroid men. We further combined NAFLD with ALT levels and with the FIB-4 index.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…3 Two Chinese studies and one Dutch study found a positive association between high-normal FT3 levels and NAFLD, where the latter used the fatty liver index to identify NAFLD. [8][9][10] Our results documented this positive association in euthyroid women but not in euthyroid men. We further combined NAFLD with ALT levels and with the FIB-4 index.…”
Section: Discussionsupporting
confidence: 50%
“…4,5 However, the conclusions from the studies regarding the association of free triiodothyronine (FT3), the bioactive form of thyroid hormones, with NAFLD in euthyroid subjects remained inconsistent. [6][7][8][9] Previous studies in Chinese 8,10 and Dutch people 9 showed that high-normal FT3 levels were associated with the risk of NAFLD, but other studies did not find the same association. 6,7 In addition, most of the studies showed that lower free thyroxine (FT4) 6,7,9 and higher TSH 7,9,10 levels within the normal range were associated with the risk of NAFLD in euthyroid adults.…”
Section: Introductionmentioning
confidence: 97%
“…4,20 Free triiodothyronine has been positively related to body fat mass and various metabolic parameters. [21][22][23][24][25] A higher FT3 was associated with an enlarged waist circumference in study among U.S. people 22 and in the Lifelines Cohort study in the Netherlands. 25 Roef et al 24 reported T A B L E 5 Odds ratios for metabolic syndrome according to the deciles of TSH levels and FT3/FT4 ratios positive associations of FT3 with BMI, fat mass and insulin resistance assessed by HOMA-IR in healthy euthyroid young men.…”
Section: Ft3/ft4 Ratio Can Predict Metabolic Syndrome Better Than Tshmentioning
confidence: 81%
“…The effect was mediated by body composition changes and by the fat-associated hormone leptin rather than androgen deficiency. Another study interrelated non-alcoholic fatty liver disease with higher fT3 concentrations in euthyroid subjects, probably consequent to central obesity (197). Both central and peripheral components of the feedback loop are apparently involved in the reactive adjustments to obesity (Figure 7).…”
Section: Thyroid Allostasis In Various Physiological and Pathologicalmentioning
confidence: 99%